Combined treatment of rituximab, idarubicin, dexamethasone, cytarabine, methotrexate with radiotherapy for primary central nervous system lymphoma. Issue 6 (13th March 2014) - Zhao, Defeng; Qian, Liren; Shen, Jianliang; Liu, Xiaopeng; Mei, Ke; Cen, Jian; Wang, Yaming; Li, Congyong; Ma, Yuanyuan
Abstract The overall response rates and long‐term survival of primary central nervous system lymphoma (PCNSL) are still significantly inferior to the results achieved in similar subtypes of extranodal non‐Hodgkin's lymphoma. It is clearly necessary to investigate new therapeutic methods on PCNSL. We encountered three patients histologically documented PCNSL as diffuse large B‐cell lymphoma (DLBCL). They were treated with R‐IDARAM which comprised rituximab, idarubicin, dexamethasone, cytarabine and methotrexate. Patient 1 received stereotactic brachytherapy (SBT) prior to chemotherapy performed with iodine‐125 seeds (cumulative therapeutic dose 50 Gy). After six cycles of R‐IDARAM at 3‐weekly intervals, radiotherapy was applied at a dosage of 2000–4000 cGy in conventional schedule (180 or 200 cGy/day) to whole brain or spinal cord in all patients. Complete remission (CR) was achieved after first two cycles of R‐IDARAM in all patients. All three patients remained in CR at the time of this report with a median duration of follow‐up of 23 months (ranging from 13 to 41 months). Three patients have been alive for 41, 13, 16 months respectively until now. The patient with the longest survival time was the one given SBT prior to chemotherapy. This study suggests that R‐IDARAM combining with radiotherapy maybe a high effective regimen in PCNSL patients especially those with primary central nervous system DLBCL. A comprehensive treatment combining internal radiotherapy by SBT, modified R‐IDARAM and followed reduced external radiotherapy may be a new treatment concept for PCNSL with higher efficiency and lower toxicity.